Konsep Hermeneutika Sebagai Metodologi Interpretasi Teks Al-Quran - Wely Dozan; Muhammad Turmudzi (MAGHZA, 2019)
Lately, the concept of the methodology of interpreting the texts of the Qur’an is not only struggling from the history of the Companions and the Tabi'in but in understanding the Word of God it is necessary to have dialectics with the interpretation of the text with the term hermeneutics. Some contemporary interpretations make a new study of the Qur’an using the hermeneutic approach. Specifically, this paper seeks to contribute to providing concepts related to hermeneutics as a textual interpretation methodology. There are some things that are very urgent to be studied in this discussion, including, First, hermeneutics as a dialectic of text interpretation. Second, the methodology of the hermeneutic approach in understanding texts. Third, the application of hermeneutics as a text interpretation. Thus, the concept of hermeneutics in the texts is to find the Qur'anic values ​​contextually behind the meaning of the text of the verse.